?Hang Ups, Let Downs, Bad Breaks, Setbacks?: Impact of Structural Socioeconomic Racism and Resilience on Cognitive Change Over Time for Persons Racialized as Black - Paris B. Adkins-Jackson; Boeun Kim; C?sar Higgins Tejera; Tiffany N. Ford; Ariana N. Gobaud; Kyler J. Sherman-Wilkins; Indira C. Turney; Justina F. Avila-Rieger; Kendra D. Sims; Safiyyah M. Okoye; Daniel W. Belsky; Tanisha G. Hill-Jarrett; et al. (Mary Ann Liebert, 2024)
Introduction: Older adults racialized as Black experience higher rates of dementia than those racialized as White. Structural racism produces socioeconomic challenges, described by artist Marvin Gaye as ?hang ups, let downs, bad breaks, setbacks? that likely contribute to dementia disparities. Robust dementia literature suggests socioeconomic factors may also be key resiliencies. Methods: We linked state-level data reflecting the racialized landscape of economic opportunity across the 20th Century from the U.S. Census (1930?2010) with individual-level data on cognitive outcomes from the U.S. Health and Retirement Study participants racialized as Black. A purposive sample of participants born after the Brown v. Board ruling (born 1954?59) were selected who completed the modified Telephone Interview for Cognitive Status between 2010 and 2020 (N=1381). We tested associations of exposure to structural racism and resilience before birth, and during childhood, young-adulthood, and midlife with cognitive trajectories in mid-late life using mixed-effects regression models. Results: Older adults born in places with higher state-level structural socioeconomic racism experienced a more rapid cognitive decline in later life compared to those with lower levels of exposure. In addition, participants born in places with higher levels of state-level structural socioeconomic resilience experienced slower cognitive change over time than their counterparts. Discussion: These findings reveal the impact of racist U.S. policies enacted in the past that influence cognitive health over time and dementia risk later in life.